Operational characteristics of city bus services in ipoh route-ipoh-bercham - Aisyah Safiyah binti Yob Sa'ed, Aisyah Safiyah (2010)
The objective of this study is to obtain the operational characteristics of city bus services in lpoh and to compare it with urban transit design calculation. The next objective is to measure the level of service (LOS) of the service based on the obtained operational characteristics. The last objective of this study is to gain basic passengers' characteristics and their perception on the bus service.